Charting Nigerian Waters for Safer Navigation - Egbuh, Innocent N. (The International Hydrographic Review, 2006)
In pursuit of Nigeria’s, international obligations on maritime safety, the elimination of dangers to search and rescue efforts in our coastal waters, environmental pollution and destruction of maritime habitats, and hide-out for sea-borne criminal elements, the Federal Ministry of Transport through the National Maritime Authority (NMA), entered into an agreement on June 16, 2003, with Humber Marine Werks Limited (HMW) for Consultancy on Removal of Wrecks and Derelicts in Nigerian Waterways aimed the contract to conduct a hydrographic survey of the Lagos Ports Area; a critical input to quotations for actual removal of wrecks by contractors to be nominated by the Ministry.